2018
DOI: 10.1108/hrmid-06-2017-0101
|View full text |Cite
|
Sign up to set email alerts
|

Managing employees with chronic illness

Abstract: Purpose The purpose of this paper is to identify future directions for human resource managers to provide work accommodations to chronically ill employees. Design/methodology/approach The authors researched empirical studies in management, occupational health journals, and reports on chronically ill employees. Findings The paper provides research-based practical insights for human resource practitioners to deal with the growing number of chronically ill employees. Practical implications The paper highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This current study further demonstrates the complexities associated with the disclosure of one or more long-term conditions to work colleagues and/or supervisors (Singh et al, 2018). No other studies were found which specifically compared disclosure of long-term conditions among medical officers, nurses, midwives and allied health professional staff.…”
Section: Introductionmentioning
confidence: 54%
“…This current study further demonstrates the complexities associated with the disclosure of one or more long-term conditions to work colleagues and/or supervisors (Singh et al, 2018). No other studies were found which specifically compared disclosure of long-term conditions among medical officers, nurses, midwives and allied health professional staff.…”
Section: Introductionmentioning
confidence: 54%
“…An additional challenge is that those with chronic illness may not be sure whom to turn to for support to make work‐related decisions; they may have more knowledge about the impact of their illness on work than their human resources department (Singh et al., 2018); and they may fear how disclosure could be used against them in the workplace, thereby making colleagues and supervisors potentially unsafe spaces for processing the impact of their illness (Royster & Marshall, 2008; Raque et al., 2021). Further, health care staff and supports (e.g., nurse navigators and social workers) may not be able to give them the concrete answers related to work that workers are seeking.…”
Section: Chronic Health Issues and Workmentioning
confidence: 99%
“…Workplace culture may be reimagined to better integrate the diverse needs of all employees, including those with health concerns. Motivations for organizations to address workplace discrimination include increasing productivity, improving worker attitudes and well‐being, fostering inclusive work culture, and avoiding discrimination claims (McGonagle et al., 2016; Singh et al., 2018).…”
Section: Psychology Of Working Theorymentioning
confidence: 99%
“…Chronically ill employees (CIEs) constitute the fastest growing, and one of the largest, minority segments at work worldwide (Singh et al , 2018), contributing up to a quarter of the EU workforce in 2017 (Eurofound, 2019). Physical chronic illnesses (such as diabetes, coronary heart disease, cancer and arthritis) are of long duration, slow progression and can last for decades.…”
Section: Introductionmentioning
confidence: 99%